FIRM CREATED VERSUS USER GENERATED: WHICH DRIVES CONSUMER PURCHASE INTENTION ON SNACK BAR PRODUCTS? - Whanarahardja, Ingrid; Setiyaningrum, Ari (STIE Pelita Nusantara Semarang, 2024)
This study aims to examine the influence of firm created social media communication and user generated social media communication on purchase intention directly and indirectly through the mediation of brand awareness and brand passion. The research model was tested on Fitbar brand snack bar products. Primary data was obtained through a survey of 150 respondents. Sampling was carried out with a nonprobability-purposive sampling approach. The results of the hypothesis test using SEM-PLS indicated that firm created social media communication and user generated social media communication had no direct effect on purchase intention. Firm created social media communication was found to influence brand awareness, while user generated social media communication had no effect on brand awareness. Firm created social media communication and user generated social media communication were found to influence brand passion. Brand awareness was found to have no effect on purchase intention, while brand passion influenced purchase intention. The results of the mediation test prove that brand awareness does not mediate the influence of firm created social media communication and user generated social media communication on purchase intention, while brand passion is able to mediate the influence of firm created social media communication and user generated social media communication on purchase intention.